Neuroimaging in alcohol use disorder: From mouse to man. Issue 5 (22nd April 2019) - Fritz, Michael; Klawonn, Anna M.; Zahr, Natalie M.
Abstract: This article provides an overview of recent advances in understanding the effects of alcohol use disorders (AUD) on the brain from the perspective of magnetic resonance imaging (MRI) research in preclinical models and clinical studies. As a noninvasive investigational tool permitting assessment of morphological, metabolic, and hemodynamic changes over time, MRI offers insight into the dynamic course of alcoholism beginning with initial exposure through periods of binge drinking and escalation, sobriety, and relapse and has been useful in differential diagnosis of neurological diseases associated with AUD. Structural MRI has revealed acute and chronic effects of alcohol on both white and gray matter volumes. MR Spectroscopy, able to quantify brain metabolites in vivo, has shed light on biochemical alterations associated with alcoholism. Diffusion tensor imaging permits microstructural characterization of white matter fiber tracts. Functional MRI has allowed for elucidation of hemodynamic responses at rest and during task engagement. Positron emission tomography, a non‐MRI imaging tool, has led to a deeper understanding of alcohol‐induced receptor and neurotransmitter changes during various stages of drinking and abstinence. Together, such in vivo imaging tools have expanded our understanding of the dynamic course of alcoholism including evidence for regional specificity of the effects of AUD, hints at mechanisms underlying the shift from casual to compulsive use of alcohol, and profound recovery with sustained abstinence.